The Relationship of Librarian Service Quality and Library Anxiety among Visitors at the Padang State University Library - Naura Salsabila Afrizal; Rini Asmara (Darul Yasin Al Sys, 2026)
The advancement of information technology in academic libraries requires improvements in service quality that extend beyond technical performance to address users’ psychological experiences. However, library anxiety remains a persistent issue that may hinder users’ optimal engagement with library services. This study aims to examine the relationship between librarian service quality and library anxiety among users of the Universitas Negeri Padang Library. A quantitative approach with a correlational research design was employed. The study population consisted of 40,432 library visitors, from which 100 respondents were selected using simple random sampling. Data were collected through a structured Likert-scale questionnaire developed based on the SERVQUAL model for measuring service quality and the Multidimensional Library Anxiety Scale (MLAS) for assessing library anxiety. The data were analyzed using Pearson correlation with the assistance of SPSS software. The findings indicate that librarian service quality was categorized as good, with an average score of 3.15, whereas library anxiety was relatively low, with an average score of 2.28. Pearson correlation analysis revealed a strong and statistically significant negative relationship between librarian service quality and library anxiety, with a correlation coefficient of -0.679 and a significance level of <0.001. This result indicates that higher librarian service quality is associated with lower levels of user anxiety. Furthermore, the coefficient of determination (R²) of 46.1% suggests that service quality contributes substantially to reducing library anxiety, although other external factors may also influence users’ psychological experiences. The study concludes that librarian service quality plays a crucial role in creating a psychologically supportive, accessible, and user-friendly academic library environment. These findings contribute to the literature on service quality and user behavior in library science and offer practical implications for library management, particularly in strengthening empathy, communication, and user assistance to minimize library anxiety.